2011
DOI: 10.1007/s00044-011-9680-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antihypertensive activity evaluation in spontaneously hypertensive rats of lacidipine analogues

Abstract: Six analogues of lacidipine, (E)-diethyl 4-(2-(3-amino)-3-oxoprop-1-enyl)phenyl-2, 6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylates (compounds 1-6), were synthesized and their antihypertensive effects in spontaneously hypertensive rats were evaluated by ig administration. Amongst the tested compounds, compound 5 exhibited the highest antihypertensive effect. The lasting time and potency of compound 5 showed a dose-dependent manner. The results suggested that N-tert-butyl acrylamide moiety at 2 0 -position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results showed that 1.0 mg/kg CZ454 lowered systolic and diastolic blood pressures by almost 20 %. Furthermore, in the previous study, it was confi rmed that antihypertension of CZ454 could last 24 h [ 16 ] . Calcium channel blockers can impede voltage-gated calcium channels, inhibit the entry of extracellular calcium, relax vascular smooth muscle, and lower blood pressure.…”
mentioning
confidence: 91%
“…The results showed that 1.0 mg/kg CZ454 lowered systolic and diastolic blood pressures by almost 20 %. Furthermore, in the previous study, it was confi rmed that antihypertension of CZ454 could last 24 h [ 16 ] . Calcium channel blockers can impede voltage-gated calcium channels, inhibit the entry of extracellular calcium, relax vascular smooth muscle, and lower blood pressure.…”
mentioning
confidence: 91%